Desarrollo de un Sistema Gestor Documental Electrónico (GDE) para el Gad Municipal del Cantón Tisaleo. - Moreno Quimbita, Karen Dayana (2021)
Currently, there are various versions of document management systems in the world, starting from a manually created record for handling incoming and outgoing correspondence, up to the most up-to-date computer systems that have been designed for the use not only of the administrative documentation, but also of the prioritization of the use of paper by replacing them with electronic formats, it is also important to mention that they have come to control the workflows in the process of processing important documentation handled by various entities, in turn capturing information from a production database, linking content from files, documentation centers, among others, which allow information to be retrieved from anywhere and searches quickly and optimally.